Mika : My New Life : Lotus Lane #4 - May, Kyla (New York, NY : Scholastic Inc., 2013)
Japanese American Mika is the newest member of the Lotus Lane Girls, with her very own new diary, but she is still troubled by tensions between her different friends, and worried about her project for the school newspaper.
Appeals to 1st-3rd graders.
Reading level grade 2.
Keywords: Japanese American families -- Juvenile fiction; Student newspapers and periodicals -- Juvenile fiction; Diaries -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Elementary schools -- Juvenile fiction; Japanese Americans -- Fiction; Family life -- Fiction; Newspapers -- Fiction; Diaries -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Elementary schools -- Fiction; Schools -- Fiction; Diary fiction